<meta http-equiv="refresh" content="1; url=/nojavascript/"> Notation for Transformations ( Read ) | Analysis | CK-12 Foundation
Dismiss
Skip Navigation

Notation for Transformations

%
Best Score
Practice
Best Score
%
Practice Now
Point Notation and Function Notation
 0  0  0

When performing multiple transformations, it is very easy to make a small error. This is especially true when you try to do every step mentally. Point notation is a useful tool for concentrating your efforts on a single point and helps you to avoid making small mistakes. 

What would f(3x) + 7  look like in point notation and why is it useful? 

Watch This

http://www.youtube.com/watch?v=An29CALYjAA James Sousa: Function Transformations: A Summary

Guidance

A transformation can be written in function notation and in point notation. Function notation is very common and practical because it allows you to graph any function using the same basic thought process it takes to graph a parabola in vertex form. 

Another way to graph a function is to transform each point one at a time. This method works well when a table of  x, y values is available or easily identified from the graph. 

Essentially, it takes each coordinate  (x, y) and assigns a new coordinate based on the transformation. 

(x, y) \rightarrow (new \ x, new \ y)

The new  y coordinate is straightforward and is directly from what takes place outside f(x)  because f(x)  is just another way to write y . For example,  f(x) \rightarrow 2f(x) - 1 would have a new  y coordinate of 2y-1

The new  x coordinate is trickier. It comes from undoing the operations that affect x

For example, f(x) \rightarrow f(2x -1)  would have a new  x coordinate of \frac{x +1}{2}

Example A

Convert the following transformation into function notation and point notation.  Then, apply the transformation to the three points in the table. Transformation: Horizontal shift right three units, vertical shift up 4 units.

x

y

1

3

2

5

8

-11

Solution:

f(x) \rightarrow f(x-3)+4

(x,y) \rightarrow (x+3,y+4)

Note that the operations with the  x are different. The point notation is a straightforward approach to apply the transformation. 

Example B

Convert the following function notation into point notation and apply it to the included table of points. 

f(x) \rightarrow \frac{1}{4} f(-x-3)-1

x

y

0

0

1

4

2

8

Solution: The  y component can be directly observed. For the  x component you need to undo the argument.  (x, y) \rightarrow  \left ( - x-3,\frac{1}{4} y-1 \right )

Note: Point notation greatly reduces the mental visualization required to keep all the transformations straight at once. 

Example C

Convert the following point notation to words and to function notation and then apply the transformation to the included table of points. 

(x+3,y-1) \rightarrow (2x+6,-y)

x

y

10

8

12

7

14

6

Solution: This problem is different because it seems like there is a transformation happening to the original left point. This is an added layer of challenge because the transformation of interest is just the difference between the two points. Notice that the  x coordinate has simply doubled and the  y coordinate has gotten bigger by one and turned negative. This problem can be rewritten as:

(x,y) \rightarrow (2x,-(y+1) )=(2x,-y-1)

f(x) \rightarrow - f \left ( \frac{x}{2} \right )-1

Concept Problem Revisited

The function f(3x) +7  would be written in point notation as (x, y) \rightarrow \left (\frac{x}{3}, y+7 \right ) . This is useful because it becomes obvious that the  x values are all divided by three and the  y values all increase by 7. 

Vocabulary

Notation is a mathematical convention that helps others read your work. It is supposed to be designed to help aid your thinking, but when misunderstood can cause great confusion. 

Guided Practice

1. Convert the following function notation into words and then point notation. Finally, apply the transformation to three example points. 

f(x) \rightarrow - 2f(x-1) + 4

2. Convert the following function in point notation to words and then function notation. 

(x,y)\rightarrow(3x+1,-y+7)

3. Convert the following function in function notation to words and then point notation. 

f(x)\rightarrow -\frac{1}{2} f(x-1)+3

Answers:

1. f(x) \rightarrow - 2f(x-1) + 4

Vertical reflection across the  x axis. Vertical stretch by a factor of 2. Vertical shift 4 units. Horizontal shift right one unit. 

(x,y)\rightarrow(x+1,- 2y+4)

2. (x,y)\rightarrow(3x+1,-y+7)

Horizontal stretch by a factor of 3 and then a horizontal shift right one unit. 

Vertical reflection over the  x axis and then a vertical shift 7 units up. 

f(x)\rightarrow -f \left ( \frac{1}{3}x - \frac{1}{3} \right ) +7

3. f(x)\rightarrow -\frac{1}{2} f(x-1)+3

Vertical reflection across the  x axis, stretch by a factor of \frac{1}{2}  and shift up 3. Horizontal shift right 1 unit. 

(x, y) \rightarrow \left ( x+1, -\frac{1}{2}y+3 \right )

Practice

Convert the following function notation into words and then point notation. Finally, apply the transformation to three example points.

x

y

0

5

1

6

2

7

1. f(x) \rightarrow -\frac{1}{2} f(x+1)

2. g(x)\rightarrow 2g(3x)+2

3. h(x) \rightarrow - h(x-4)-3

4. j(x) \rightarrow 3j(2x-4)+1

5. k(x)\rightarrow -k(x-3)

Convert the following functions in point notation to function notation. 

6. (x,y) \rightarrow \left ( \frac{1}{2} x+3,y-4 \right )

7. (x,y) \rightarrow (2x+4,-y+1)

8. (x,y) \rightarrow (4x,3y-5)

9. (2x,y) \rightarrow (4x, - y+1)

10. (x+1,y-2) \rightarrow (3x+3, -y+3)

Convert the following functions in function notation to point notation. 

11. f(x) \rightarrow 3f(x-2)+1

12. g(x) \rightarrow -4g(x-1)+3

13. h(x) \rightarrow \frac{1}{2} h(2x+2)-5

14. j(x) \rightarrow 5j \left ( \frac{1}{2} x-2 \right )-1

15. k(x) \rightarrow \frac{1}{4} k(2x-4)

Image Attributions

Reviews

Email Verified
Well done! You've successfully verified the email address .
OK
Please wait...
Please wait...
ShareThis Copy and Paste

Original text